COMMERCIAL LOGISTICS LEGISLATION IN THE EUROPEAN UNION – BASIC ISSUES - Daniela Marasová; Vladimír Taraba (Perner’s Contacts, 2011)
The article primarily deals with the issue of the European law in the field of free movement of goods, which may include to the legislation of commercial logistics. It also defines of the basic principles supporting this freedom, including relations among individual member states when applying this freedom. In the article the attention is also paid to mutual acknowledgement of products and the rule of reason as the method of prevention against abuse of various protective measures of individual member states that would disable effective operation of a company’s commercial logistics.